Semiological signs for the diagnosis of acute appendicitis: case report and literature review - de Almeida Barbosa, Cirênio; Fonseca Guimarães, Mariana; Almeida da Silva, Rafaela; Soares dos Santos, Ronald; Clara Guimarães Gabrich Fonseca, Ana; Chaves Moreira, Weber (Seven Editora, 2023)
Inflammation of the vestigial vermiform appendix is one of the main causes of acute abdomen in emergency departments. Clinical manifestations may vary according to the patient’s age, position and size of the appendix. The diagnosis is eminently clinical, and may present laboratory and imaging alterations, contributing to diagnostic confirmation. In view of the variety of clinical manifestations and differential diagnoses of the acute abdomen, the diagnosis can be challenging. Considering that the late recognition of this condition can lead to serious complications, one should be clear about the possible clinical, laboratory and imaging findings. With that, the objective of this work was to present a clinical case and a review of the literature on the clinical findings present in acute appendicitis, contributing to the early diagnosis. To support the work, current bibliographical references were used, searching for articles in the PubMed, Scielo and Lilacs databases. DOI: https://doi.org/10.56238/devopinterscie-151